Enhancing the well-being of high school students through comprehensive reproductive health education - Lintang Widya Sishartami; Kiky Martha Ariesaka; Anditri Weningtyas; Hilma Tsurayya Iftitahurroza; Arif Ladika; Fannia Yosa Bakhtiar; Faridatus Solikha (Journal of Community Service and Empowerment)
This activity aimed to enhance high school students' knowledge of reproductive health through counseling using lectures and booklet distribution. The program was conducted at a high school in Malang City, involving 45 eleventh-grade students. The methods used included a pre-test, lecture, booklet distribution, and a post-test. The analysis results showed a significant increase in students' knowledge of reproductive health after the intervention, with the pre-test score rising from 24.13±1.74 to a post-test score of 28.64±0.77 (p=0.000). This counseling session successfully raised adolescents' awareness and knowledge of reproductive health, helping prevent issues such as sexually transmitted infections and early pregnancies. The use of booklets proved to be an effective medium for delivering accurate and comprehensive information on reproductive health.